Financial aspects of Arab power development - Alami, R (Oxford Institute for Energy Studies, 2004)
This study examines inter-linkages between the financing and development of Arab power sectors. These sectors are now operating in a difficult global financial market characterised by investors' retrenchment and risk aversion. This market has also moved away from the notion of a struggle between private and public finance, towards a strategy that emphasises the co-ordination of public, private, and multilateral players, to ensure successful delivery of services. Consequently, the current modus operandi in funding power projects worldwide is 'hybrid forms of co-operation'. Recently, Arab power sectors have witnessed the entry of private sponsors and financiers, both domestic and foreign, as a result of two policy responses. Firstly, power sector regulations were adjusted to allow private operators to participate in power generation. Secondly, the reform and development of Arab financial sectors allowed an expansion of participation by Arab banks, the use of new instruments, and the entry of new players. Though the change is not overwhelming quantitatively, it allowed private power to make a palpable contribution to the expansion of power generation capacity. Arab power infrastructure will also benefit from a number of intra-regional power pools and grid inter-connection projects, whose financing has been led by multilateral regional funds. Thus, there is a case for pursuing policies that build on the region’s strength and match the current emphasis on resource pooling, namely: strengthening regional co-operation; maintaining flexibility about the range of sponsors allowed to operate; furthering financial development. Conversely, power sector financing should shift away from an emphasis on supply shortages, towards managing demand and addressing operational and qualitative deficiencies. Similarly, sectoral reforms should be comprehensive enough to deal with underlying social and political dimensions. Given the embryonic state of regional reforms and of international experiences, financial problems will neither be solved quickly nor by one-off measures of price correction or asset sale.